2014
DOI: 10.1021/nn502887j
|View full text |Cite
|
Sign up to set email alerts
|

Distance and Plasmon Wavelength Dependent Fluorescence of Molecules Bound to Silica-Coated Gold Nanorods

Abstract: Plasmonic nanoparticles can strongly interact with adjacent fluorophores, resulting in plasmon-enhanced fluorescence or fluorescence quenching. This dipolar coupling is dependent upon nanoparticle composition, distance between the fluorophore and the plasmonic surface, the transition dipole orientation, and the degree of spectral overlap between the fluorophore's absorbance/emission and the surface plasmon band of the nanoparticles. In this work, we examine the distance and plasmon wavelength dependent fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
439
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(463 citation statements)
references
References 65 publications
23
439
0
1
Order By: Relevance
“…Recently, several works have reported that the result of investigations of the distance and plasmon wavelength dependent fluorescence of fluorophore via nanorod or nanoparticle substrate [85,86]. In particular, core-shell configuration, precisely controlling the distance between fluorophore and plasmonic nanostructure, have been widely used in the investigation of PEF effect recently [87][88][89][90]. It is found that by introduction of silica shell with various thicknesses to isolated fluorophore Au nanoparticles (AuNPs) and four different target molecules with different absorbance properties, the investigation of fluorescence quenching effect from complete quenching to no coupling was comprehensively carried out.…”
Section: The Wavelength and Spacer Effect Towards The Fluorescence Enmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several works have reported that the result of investigations of the distance and plasmon wavelength dependent fluorescence of fluorophore via nanorod or nanoparticle substrate [85,86]. In particular, core-shell configuration, precisely controlling the distance between fluorophore and plasmonic nanostructure, have been widely used in the investigation of PEF effect recently [87][88][89][90]. It is found that by introduction of silica shell with various thicknesses to isolated fluorophore Au nanoparticles (AuNPs) and four different target molecules with different absorbance properties, the investigation of fluorescence quenching effect from complete quenching to no coupling was comprehensively carried out.…”
Section: The Wavelength and Spacer Effect Towards The Fluorescence Enmentioning
confidence: 99%
“…It is found that by introduction of silica shell with various thicknesses to isolated fluorophore Au nanoparticles (AuNPs) and four different target molecules with different absorbance properties, the investigation of fluorescence quenching effect from complete quenching to no coupling was comprehensively carried out. It is found that the energy transfer from the fluorophore to the metal substrate plays a critical role in fluorescence quenching phenomenon, as shown in Figure 11 [89].…”
Section: The Wavelength and Spacer Effect Towards The Fluorescence Enmentioning
confidence: 99%
“…181 Among the most investigated strategies is the use of core shell nanostructures with metal core and silica based shell, which provides also a good possibility of spacing control between the dyes and the metallic surface. [183][184][185][186][187][188][189][190][191][192] The dye can be either directly incorporated in the silica shell during the synthesis of post-grafted at the surface of the silica. M. A. Noginov used this configuration to generate coreshell structure functionalized at the surface by Oregon green 488 fluorophore encapsulated in the outer silica shell.…”
Section: Technology Driven Exploration Of Hybrid Materialsmentioning
confidence: 99%
“…The adjustment of plasmon resonance peaks has been extensively reported [41,41,43], as well as highly sensitive SPR detection methods using functionalized anisotropic Au NPs [42,43]. The SPR peaks can be altered by variation of the Au NR aspect ratios, for example changing the CTAB concentration [44].…”
Section: Advanced Topics In Crystallization 194mentioning
confidence: 99%